2022
DOI: 10.1590/1678-4324-2022220315
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality and Safety of Some Dried Spices Obtained from Markets, Spice Shops and Homes

Abstract: This study was conducted to determine both the microbiological quality and safety of the spices as well as whether or not there are any pathogenic bacteria in fifty-four samples of six dried spices supplied from three markets, three spice shops, and three homes. Total mesophilic aerobic bacteria (TMAB), aerobic spore former bacteria (ASFB), total yeast-mold (TYM), coliform group bacteria (CGB), Escherichia coli (E. coli), and Staphylococcus aureus (S. aureus), and Salmonella spp. were found in red pepper flake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…coli, a commensal organism is the most common coliform bacteria that are associated with spices. [15][16][17][18][19] Contamination of coliforms in spices indicates poor sanitary or careless handling practices by spice handlers, improper facility design, the use of non-potable water during processing, mix-ups and cross contaminations, all of which results in opportunistic illnesses. In the present study, though E. coli was absent in all the spice samples, 24 (17.14 %) of the 140 samples tested positive for total coliforms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…coli, a commensal organism is the most common coliform bacteria that are associated with spices. [15][16][17][18][19] Contamination of coliforms in spices indicates poor sanitary or careless handling practices by spice handlers, improper facility design, the use of non-potable water during processing, mix-ups and cross contaminations, all of which results in opportunistic illnesses. In the present study, though E. coli was absent in all the spice samples, 24 (17.14 %) of the 140 samples tested positive for total coliforms.…”
Section: Discussionmentioning
confidence: 99%
“…20 Globally, many recent studies reported the occurrence of Salmonella, a bacteria of particular public health concern. 16,21,22 A study investigated that imported herbs and spices accounted for 1,677 cases i.e., 16% of all foodborne illnesses in the United States between 1996 and 2014. 23 Furthermore, the FDA determined that imported dried spices had a contamination rate of 6.6% between 2007 and 2009 and also according to the researchers, the contamination rate has been relatively constant over the last three decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Palmas, Tocantins (Walker et al, 2014), Amazon region of Brazil, absence was found in garlic and oregano samples. Ogur (2022) in Turkey, determining the microbiological quality and safety of spices, found E. coli, S. aureus and Salmonella spp. in red pepper flakes, black pepper, dried mint, dried thyme and ground cumin.…”
Section: Bacterial Isolationmentioning
confidence: 99%